2021
DOI: 10.1111/bju.15540
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial investigating clinical outcomes and stent‐related symptoms after placement of a complete intra‐ureteric stent on a string versus conventional stent placement

Abstract: To compare stent-related symptoms (SRS) associated with conventional ureteric JJ stent (CUS) placement and SRS associated with placement of a modified complete intra-ureteric stent (CIUS) with extraction suture, designed to minimize SRS, using the validated Ureteral Stent Symptom Questionnaire (USSQ). Materials and MethodsWe randomized 124 patients who had undergone uncomplicated ureteroscopic lithotripsy into a CIUS and a CUS placement group. USSQ scores were evaluated on postoperative days 1 and 7 (just befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Removal of the ureteral stent with extraction string was significantly less painful than with cystoscope (mean VAS scores 5.67 vs 2.73; p < 0.001) [ 12 ]. In a recent study, Shah et al compared stent-related complications with the placement of a conventional ureteral stent and a complete intra-ureteric stent with extraction string and showed that no difference in complication rates between the two groups [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Removal of the ureteral stent with extraction string was significantly less painful than with cystoscope (mean VAS scores 5.67 vs 2.73; p < 0.001) [ 12 ]. In a recent study, Shah et al compared stent-related complications with the placement of a conventional ureteral stent and a complete intra-ureteric stent with extraction string and showed that no difference in complication rates between the two groups [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The same results were found in our study ( p = 1.00). Shah et al reported a 5% rate of stent migration and accidental dislodgement [ 30 ]. In the present study, we found that 1.5% (one female) of patients with an extraction string prematurely removed the ureteral stent.…”
Section: Discussionmentioning
confidence: 99%
“…Although a few studies which compared conventional DJ stents to complete intraureteral stents have demonstrated a reduction in SRS, enhancement of QoL, and less stent-related discomfort [ 20 , 21 , 22 ], a similar study that was conducted at our institute found a reduction in symptom scores across LUTS domains of the USSQ, but the reduction was not statistically significant [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among women who were stented, individual domains of the FSFI—the Arousal, Orgasm, and Satisfaction subdomains—were statistically lower in the stented group [ 24 , 25 , 26 ]. Meanwhile, studies involving complete intraureteral stents with extraction strings by Kim et al [ 27 ] and Shah M et al [ 23 ] demonstrated a general drop in sexual activity among patients following placement of a stent with extraction strings due to stent-related pain, anxiety of stent dislodgement, or a thread dangling from the urethral meatus.…”
Section: Discussionmentioning
confidence: 99%
“…Vogt and colleagues introduced pigtail suture stents (PSS) in 2015, replacing the DJ distal pigtail with a suture thread reaching the bladder [ 6 ]. This device was later investigated by randomized controlled studies (RCT) which assessed more tolerability compared to conventional DJ [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%